Fine motor skills in adult Tourette patients are task-dependent - Neuner Irene; Arrubla Jorge; Ehlen Corinna; Janouschek Hildegard; Nordt Carlos; Fimm Bruno; Schneider Frank; Shah N; Kawohl Wolfram (BMC Neurology, 2012)
Abstract Background Tourette syndrome is a neuropsychiatric disorder characterized by motor and phonic tics. Deficient motor inhibition underlying tics is one of the main hypotheses in its pathophysiology. Therefore the question arises whether this supposed deficient motor inhibition affects also voluntary movements. Despite severe motor tics, different personalities who suffer from Tourette perform successfully as neurosurgeon, pilot or professional basketball player. Methods For the investigation of fine motor skills we conducted a motor performance test battery in an adult Tourette sample and an age matched group of healthy controls. Results The Tourette patients showed a significant lower performance in the categories steadiness of both hands and aiming of the right hand in comparison to the healthy controls. A comparison of patients’ subgroup without comorbidities or medication and healthy controls revealed a significant difference in the category steadiness of the right hand. Conclusions Our results show that steadiness and visuomotor integration of fine motor skills are altered in our adult sample but not precision and speed of movements. This alteration pattern might be the clinical vignette of complex adaptations in the excitability of the motor system on the basis of altered cortical and subcortical components. The structurally and functionally altered neuronal components could encompass orbitofrontal, ventrolateral prefrontal and parietal cortices, the anterior cingulate, amygdala, primary motor and sensorimotor areas including altered corticospinal projections, the corpus callosum and the basal ganglia.